Glyptic Evidence for a Connection between Iran, Syro-Palestine and Egypt in the Fourth and Third Millennia - Teissier, Béatrice
Common motifs: Tête-bêche. Animal protomes. Griffin. Animals on Snakes. Rosette entwined by serpents. Lion attacking quadruped. Bird perched on animal. Suckling motif. Animals with extra long goatees or tails; "five-legged" animals. Exaggerated curved horns. Three pronged tails. Three pronged hands